Internet Marketing, 4th Edition - Debra Zahay; Mary Lou Roberts (Cengage Learning, 2018)
INTERNET MARKETING provides comprehensive coverage of the rapidly changing field of Internet marketing that is timely and relevant. It relies on extant marketing theory where appropriate and introduces many conceptual frameworks to structure student understanding of Internet marketing issues. Above all, it works on the premise that the Internet--whether used as a medium of communication or as a channel of distribution--is only one component of the contemporary marketer's arsenal. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.